2013
DOI: 10.3109/02656736.2013.841327
|View full text |Cite
|
Sign up to set email alerts
|

Approaches for modelling interstitial ultrasound ablation of tumours within or adjacent to bone: Theoretical and experimental evaluations

Abstract: Purpose The objectives of this study were to develop numerical models of interstitial ultrasound ablation of tumors within or adjacent to bone, to evaluate model performance through theoretical analysis, and to validate the models and approximations used through comparison to experiments. Methods 3D transient biothermal and acoustic finite element models were developed, employing four approximations of 7 MHz ultrasound propagation at bone/soft tissue interfaces. The various approximations considered or exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 65 publications
0
23
0
Order By: Relevance
“…This model was experimentally validated by our group in bone/soft tissue phantoms and in ex vivo bones and soft tissues, through comparison to temperature distributions derived both invasively and using MRTI [38, 47, 48]. Q=2αI=2TαIsrtre2rtrμdr where α is the ultrasound absorption coefficient (Np/m), I is acoustic intensity (W/m 2 ), scriptT is the transmission coefficient (unitless), I s is the acoustic intensity on the transducer surface (W/m 2 ), r t is the transducer radius (m), r is the radial distance from the transducer's central axis (m), and μ is the ultrasound attenuation coefficient (Np/m).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This model was experimentally validated by our group in bone/soft tissue phantoms and in ex vivo bones and soft tissues, through comparison to temperature distributions derived both invasively and using MRTI [38, 47, 48]. Q=2αI=2TαIsrtre2rtrμdr where α is the ultrasound absorption coefficient (Np/m), I is acoustic intensity (W/m 2 ), scriptT is the transmission coefficient (unitless), I s is the acoustic intensity on the transducer surface (W/m 2 ), r t is the transducer radius (m), r is the radial distance from the transducer's central axis (m), and μ is the ultrasound attenuation coefficient (Np/m).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the high acoustic absorption coefficient of bone, one to two orders of magnitude above that of soft tissue [35], limits energy penetration and produces significant heating at the bone surfaces [36]. Thus, bone adjacent to or encapsulating a tumour may effectively isolate the acoustic energy and effectively produce a secondary heat source away from the ultrasound applicator, enhancing heating [37, 38]. Bone adjacent to a tumour can also serve to protect nearby sensitive structures, such as the spinal cord, through acoustic and thermal insulation [18].…”
Section: Introductionmentioning
confidence: 99%
“…Tumor destruction was identified through histological staining. Simulation and ex vivo tissue studies were reported recently where performance of such interstitial ultrasound devices was characterized across a range of design parameters to explore treatments options for tumors in different locations and sizes [23]. Patient specific modeling studies were also conducted to investigate treatment delivery strategies [24], demonstrating that the interaction of ultrasound energy with surrounding bone can be used to enhance localization of therapy.…”
Section: Interstitial Cbusmentioning
confidence: 99%
“…14 3 MHz transducers (3.2 mm OD, 5 or 15 mm L) within a 4 mm ID, 4.5 mm OD catheter were also considered. It has been previously shown that acoustic heat deposition in soft tissue and bone from a cylindrical interstitial ultrasound source may be modeled as a radially divergent intensity pattern well-collimated to the length of the transducer 15,16 : (2) where is the ultrasound absorption coefficient (Np/m), is the transmission coefficient (unitless) calculated assuming normal incidence, 21 is the acoustic intensity on the transducer surface (W/m 2 ), is the transducer radius (m), is the radial distance from the transducer's axis (m), and is the ultrasound attenuation coefficient (Np/m). The absorption coefficient is assumed to be equal to the attenuation coefficient.…”
Section: Methodsmentioning
confidence: 99%